2013
DOI: 10.1002/crq.21065
|View full text |Cite
|
Sign up to set email alerts
|

Storians: Building on Indigenous Knowledge to Enhance Ni‐Vanuatu Mediative Capacity

Abstract: is article examines the elicitive style of con ict resolution training implemented in Vanuatu through the Kastom Governance Partnership, an international collaboration between Australian and Ni-Vanuatu institutions. e workshops sought to elicit and articulate a framework of managing con ict that built on kastom mediation, introduced Western con ict resolution frameworks and skills, and provided critical re ection on both. e aim of the workshops was to build the mediative capacity of Ni-Vanuatu chiefs in dealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Thus, when children interpret a behavior as a conventional act, they attend to the process of the behavior to ascertain the precise way a behavior is executed and, consequently, attempt to recreate this process by engaging in higher fidelity imitation than when imitating instrumental behaviors (Clegg & Legare, 2016;Herrmann et al, 2013;Watson-Jones, Legare, Whitehouse, & Clegg, 2014). We propose that the objective of imitating conventional behavior is social group affiliation (Nielsen & Blank, 2011;Nielsen, Simcock, & Jenkins, 2008;Uzgiris, 1981) and norm acquisition (Over & Carpenter, 2012, 2013 and not instrumental skill acquisition or physical causal learning. In the context of learning conventional behavior, the reproduction of demonstrated actions, both causally relevant and irrelevant, through high fidelity imitation is an efficient learning strategy.…”
Section: Imitative Flexibilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, when children interpret a behavior as a conventional act, they attend to the process of the behavior to ascertain the precise way a behavior is executed and, consequently, attempt to recreate this process by engaging in higher fidelity imitation than when imitating instrumental behaviors (Clegg & Legare, 2016;Herrmann et al, 2013;Watson-Jones, Legare, Whitehouse, & Clegg, 2014). We propose that the objective of imitating conventional behavior is social group affiliation (Nielsen & Blank, 2011;Nielsen, Simcock, & Jenkins, 2008;Uzgiris, 1981) and norm acquisition (Over & Carpenter, 2012, 2013 and not instrumental skill acquisition or physical causal learning. In the context of learning conventional behavior, the reproduction of demonstrated actions, both causally relevant and irrelevant, through high fidelity imitation is an efficient learning strategy.…”
Section: Imitative Flexibilitymentioning
confidence: 97%
“…Like children from other non-Western populations with low levels of Western-style education (Correa-Chávez & Rogoff, 2009; Rogoff, 2003) Ni-Vanuatu children rely on observation of adults and more capable peers to learn the skills and practices of their culture, whereas U.S. children typically learn through dyadic pedagogical interactions with adults. Additionally, Ni-Vanuatu children may experience high expectations for conformity because of the collectivist nature of Ni-Vanuatu culture (Dadkhah, Harizuka, & Mandal, 1999; Walker, 2013). Given these distinct cultural expectations for children’s learning and conformity, there are two possibilities for cultural variation between children from the United States and Vanuatu in imitative fidelity.…”
Section: Current Studymentioning
confidence: 99%
“…As such, Vanuatu is highly representative of child-rearing environments in much of the world. Socialization in Vanuatu is based on fostering collective and cooperative values with a strong emphasis on social conformity (Dadkhah, Harizuka, & Mandal, 1999; Little, Carver, & Legare, 2016; Peck & Gregory, 2005; Strachan, Samuel, & Takaro, 2007; Walker, 2013). In addition, previous work has indicated that Ni-Vanuatu children imitate behavior with higher levels of fidelity than U.S. children in experimental assessments of social learning, potentially due to differences in cultural expectations for conformity (Clegg & Legare, 2016a).…”
mentioning
confidence: 99%
“…These broader sociocultural changes have not only altered the social framework and the scope of action, e.g., in terms of economic strategies, but have also had a significant impact on traditional knowledge (Granderson, 2017). The newly introduced values and norms increasingly decoupled society from spirituality and thus procedural aspects of traditional knowledge production (Walker, 2013). Furthermore, the disintegration of traditional structures has also extinguished traditional knowledge retention.…”
Section: New Norms and Valuesmentioning
confidence: 99%